2020
DOI: 10.1186/s12964-020-00680-0
|View full text |Cite
|
Sign up to set email alerts
|

The COX-2-derived PGE2 autocrine contributes to bradykinin-induced matrix metalloproteinase-9 expression and astrocytic migration via STAT3 signaling

Abstract: Background The matrix metalloproteinase-9 (MMP-9) is up-regulated by several proinflammatory mediators in the central nervous system (CNS) diseases. Increasing reports show that MMP-9 expression is an inflammatory biomarker of several CNS disorders, including the CNS inflammation and neurodegeneration. Bradykinin (BK) is a common proinflammatory mediator and elevated in several brain injury and inflammatory disorders. The raised BK may be detrimental effects on the CNS that may aggravate brain inflammation thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…The previous studies have reported that astrocytes can be used as an in vitro model to evaluate the inflammatory processes of the CNS disorders. 8,36,37 Because, astrocytes are the most abundant glial cell type in the CNS and outnumber neurons by over fivefold. 38 They 39 The pathogenesis of brain dysfunction is multifactorial and often associated with astrocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have reported that astrocytes can be used as an in vitro model to evaluate the inflammatory processes of the CNS disorders. 8,36,37 Because, astrocytes are the most abundant glial cell type in the CNS and outnumber neurons by over fivefold. 38 They 39 The pathogenesis of brain dysfunction is multifactorial and often associated with astrocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…The bradykinin system is implicated in inflammatory responses through induction of not only vasodilation and fluid expansion but also the production of inflammatory mediators such as cytokines and prostaglandins ( 7 9 , 14 , 40 ). The bradykinin system has been implicated in a number of inflammatory events of female reproduction, including embryo implantation and ovulation ( 41 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, excessive accumulation of DABK can even evolve into a bradykinin storm resulting in severe inflammatory responses when its metabolism is left unchecked ( 9 11 ), suggesting a crucial role of bradykinin peptides in inflammation. It has been shown that BK and DABK participate in inflammation responses not only by increasing vasodilation and vascular permeability but also by stimulating the production of proinflammatory factors including cytokines and prostaglandins ( 1 , 12 – 14 ). In terms of prostaglandin synthesis, bradykinin peptides induce the expression of prostaglandin-endoperoxide synthase 2 (PTGS2), also known as cyclooxygenase-2 (COX-2), the rate-limiting enzyme in prostaglandin synthesis in various cell types ( 14 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, COX-2 is a rate-limiting enzyme that mediates the production of prostaglandin E2 (PGE2) from arachidonic acid (AA). Subsequently, PGE2 activates a JAK2/STAT3 pathway to elevate the expression of metallopeptidase 9 (MMP9) (Kawahara et al 2015 ; Lee et al 2020 ). On the other hand, our intracellular profiles (Fig.…”
Section: Discussionmentioning
confidence: 99%